Matched - Condie, Ally (New York Speak, 2010)
All her life, Cassia has never had a choice. The Society dictates everything: when and how to play, where to work, where to live, what to eat and wear, when to die, and most importantly to Cassia as she turns 17, whom to marry. When she is Matched with her best friend Xander, things couldn't be more perfect. But why did her neighbor Ky's face show up on her match disk as well?
1
NEW, LITERATURE
Keywords: Marriage -- Juvenile fiction; Mate selection -- Juvenile fiction; Self-realization -- Juvenile fiction